RESEARCH ON THE FUNCTIONAL-TECHNOLOGICAL PROPERTIES OF PROTEIN COMPLEX AND NATURAL COLOR IN THE COMPOSITION OF RESTRUCTURED HAM PRODUCTS - Iryna SHEVCHENKO (Stefan cel Mare University of Suceava, 2020)
The biopolymer complex of thermostable animal proteins (sodium caseinate, dry buttermilk, blood plasma Vepro 75 PSC), which have functional and technological properties, including stabilizing ability in the composition of restructured ham products, has been developed. The results of research confirmed the advantages of using the developed biopolymer complex, which consists of increasing water retention capability, fat-holding capacity and stabilize the physico-chemical parameters of meat products. The possibility of replacement of nitrite used to form color characteristics of meat systems with nitrate in the composition of vegetable raw materials at combination with nitrite-reducing microorganisms has been studied. The vegetable concentrate obtained from sweet potato - potato and the starter culture - Staphylococcus carnosus were used as dye. The possibility of stabilizing the color characteristics of meat raw materials in the process of pickling has been proved by applying a new kind of natural color stabilizer. The results of the study have practical importance and will help to expand the range of restructured ham products with natural ingredients.